SURVEI MINAT SISWA SMK PUSPA BANGSA KABUPATEN BANYUWANGI TERHADAP KEGIATAN EKSTRAKURIKULER FUTSAL - Asnando asnando; Angger Gorka Tejamukti; Dwi Cahyati Anggraeni (STKIP Melawi, 2023)
This research was conducted to determine students' interest in participating in futsal extracurricular activities at SMK Puspa Bangsa Banyuwangi. This study used a descriptive research design with a survey method and data collection techniques using a questionnaire. The research subjects participating in the futsal extracurricular at SMK Puspa Bangsa Banyuwangi were 37 students. The results of this study showed that students' interest in participating in futsal extracurriculars was 78.63%. from these results indicate that the interest of SMK Puspa Bangsa Banyuwangi students in participating in extracurricular activities is categorized as good.Keywords : interest, futsal extracurricular